Analyzing network performance in Universiti Malaysia Pahang Residential College Main Campus (Gambang) - Khairul Izwan, Ismail (2014)
High-speed networks allow users to use various types of services such as voice, data, image or images, video and others in a good condition or without interruption. Knowing the network performance is a necessity to get the best network performance. The purpose of this study was to investigate the mechanisms affecting traffic management network performance based on sources supplied. In preparing this research, a survey was conducted ontlie network system of Residential College University Malaysia Pahang main campus (Gambang). A study includes network delay, media access delay, traffic received, traffic sent and others by the use of the network. Wireless network system has many limitations compared to a wired network system in order to get the best performance but wireless networks system now have a place in society. This situation occurs because the wireless network system can facilitate all business and user friendly. A study conducted in this paper covers an area of wireless networks in the Residential College Universiti Malaysia Pahang Gambang campus. Wireless performance was analyzed using the OPNET Modeler 14.5. Network design of Residential College Universiti Malaysia Pahang Gambang was redesign using OPNET Modeler 14.5. The study conducted by three physical layer technologies, which is Infra-Red, Direct Sequence Spread Spectrum (DSSS) and Frequency Hopping Spread Spectrum (FSSS) with the different transfer rates.